Is forage productivity of meadows influenced by the afforestation of upstream hillsides? A study in NW Patagonia = Afecta la presencia de forestaciones ubicadas en las laderas aguas arriba de mallines su productividad forrajera? Un estudio en el Noroeste Patagónico - Weigandt, Mariana Noemi; Gyenge, Javier; Fernandez, María Elena; Varela, Santiago Agustin; Schlichter, Tomas Miguel (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (INIA), (España), 2023)
Meadows are important reserves of water, with a key role in the maintenance of the biodiversity and productivity of ecosystems. In Patagonia, Argentina, afforestation with fast-growing exotic conifers has slowly but continuously increased over recent decades; though unfortunately, knowledge of the effects of afforestation on water resources remains scarce, with no information at all related to its impact on water dynamics and productivity of meadows located downslope to it. The effects of Pinus ponderosa afforestation on water dynamics (soil moisture contents and groundwater level) and productivity (aboveground forage productivity) of Northwest Patagonia meadows under xeric and humid conditions were analyzed. In the humid meadow, gravimetric soil water content, groundwater level and forage productivity were similar downslope of forested and non-forested slopes, with a trend towards higher forage productivity on the forested slope. In the xeric meadow, gravimetric soil water content was always higher downslope of the non-forested slope, with no difference in groundwater level between treatments. Forage productivity was statistically similar between situations (downslope of forested and non-forested slopes), with a trend towards higher productivity in the zone with higher soil water content. The main difference in the latter was related to differences in soil texture between zones. These results suggest that coniferous plantations located upstream of this type of meadow do not produce a direct effect on its aboveground forage productivity. These systems have high complexity linked to precipitation, geomorphology and previous history of land use, which determine primarily soil water dynamics and consequently, forage productivity.